(untitled) (Communication & Society, 2019)
Sports media coverage of mega-events is partly oriented to gamification, the use of game elements and game design techniques in non-gaming contexts. This infotainment approach to events has been developed by media outlets as an original and effective way to capture wider audience attention and to place events in context before a competition starts. This article examines 28 gamified sports pieces developed by media outlets from seven countries during the last two Olympics (2016 Summer Olympics in Rio and 2018 Winter Olympics in Pyeongchang) and Football World Cups (2014 in Brazil and 2018 in Russia). This sample comprises two categories following Ferrer-Conill (2015): “gamified pieces” (game like elements that are part of a bigger interactive feature) and “newsgames” (more sophisticated pieces often included in complex graphics or multimedia content). The results show that, despite its entertaining formula, gamification serves mainly informational purposes and adds value to sports coverage. Especially in the Summer and Winter Olympics, gamified sports pieces tend to be explanatory and data-driven in order to inform the audience about nonmainstream sports.